2013
DOI: 10.1016/j.neuroscience.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent roles of prolactin and prolactin receptor in postoperative pain and hyperalgesia in mice

Abstract: Although surgical trauma activates the anterior pituitary gland and elicits an increase in prolactin (PRL) serum levels that can modulate nociceptive responses, the role of PRL and the PRL-receptor (PRL-R) in thermal and mechanical hyperalgesia in postoperative pain is unknown. Acute postoperative pain condition was generated with the use of the hindpaw plantar incision model. Results showed endogenous PRL levels were significantly increased in serum, operated hindpaw and spinal cords of male and female rats 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 53 publications
(77 reference statements)
1
94
0
Order By: Relevance
“…PRL can modulate the function of CNS and PNS neurons, and it plays a critical role in diverse bodily functions such as maternal behavior (48), appetite (49), sexual receptivity (50), and hypersensitivity to painful stimuli (2)(3)(4), where the action of PRL on neurons can be either acute/transient or long term. Transient effects of PRL have been characterized in many neuronal types including gonadotropin-releasing hormone neurons, tuberoinfundibular dopamine neurons, the anteroventralperiventricular nucleus, and dorsal root ganglion and TG sensory neurons (2,7,17,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PRL can modulate the function of CNS and PNS neurons, and it plays a critical role in diverse bodily functions such as maternal behavior (48), appetite (49), sexual receptivity (50), and hypersensitivity to painful stimuli (2)(3)(4), where the action of PRL on neurons can be either acute/transient or long term. Transient effects of PRL have been characterized in many neuronal types including gonadotropin-releasing hormone neurons, tuberoinfundibular dopamine neurons, the anteroventralperiventricular nucleus, and dorsal root ganglion and TG sensory neurons (2,7,17,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Because local trauma and inflammation lead to an increase in peripheral levels of PRL in female and to a lesser extent in male rats, it could be suggested that transient modulation of TRP channels by PRL in the periphery is one of underlying mechanisms for PRL-induced thermal (i.e. heat and cold) hyperalgesia (2)(3)(4). TRP channels are also involved in hypersensitivity to thermal and mechanical stimuli at presynaptic levels in the dorsal horn of the spinal cord and certain brain stem regions (62,63).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations